Effect of nitrogen and potassium fertilization on some productivity traits of Eruca sativa Mill. - الهوشي غدير; محمد عبد العزيز; حسام الدين خلاصي (Latakia University Journal -Biological Sciences Series, 2022)
A field experiment was conducted in the village of Jiebol in the countryside of Jableh city during the agricultural season 2021/2022, to study the effect of adding nitrogen fertilizer (urea 46%) at a rate of 0, 100 and 200 kg/ha, and potassium sulfate fertilizer at a rate of 0 and 100 kg/ha and the interaction between them in some Productivity traits of "local" watercress plant, the experiment was designed as a factorial experiment carried out in a randomized complete block design with three replications, and the comparison between the means was done using the least significant difference test LSD at the level of significance of 5%. The results showed a significant effect of nitrogen fertilization in all the studied traits, and the average achieved 200 kg/ha higher. The results also showed a significant effect of potassium sulfate fertilization in most of the studied traits. Addition of 100 kg/ha led to a significant increase in . The interaction between nitrogen and potassium fertilization had a significant effect on all studied traits, as the interaction 200 kg/ha urea and 100 kg/ha potassium sulfate achieved the largest rates in all studied characters.